Rapid Detection and Inhibition of SARS‐CoV‐2‐Spike Mutation‐Mediated Microthrombosis. Issue 23 (23rd October 2021) - Satta, Sandro; Lai, Angela; Cavallero, Susana; Williamson, Cayden; Chen, Justin; Blázquez‐Medela, Ana M.; Roustaei, Mehrdad; Dillon, Barbara J.; Ashammakhi, Nureddin; Carlo, Dino Di; Li, Zhaoping; Sun, Ren; et al.
Abstract: Activation of endothelial cells following severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is thought to be the primary driver for the increasingly recognized thrombotic complications in coronavirus disease 2019 patients, potentially due to the SARS‐CoV‐2 Spike protein binding to the human angiotensin‐converting enzyme 2 (hACE2). Vaccination therapies use the same Spike sequence or protein to boost host immune response as a protective mechanism against SARS‐CoV‐2 infection. As a result, cases of thrombotic events are reported following vaccination. Although vaccines are generally considered safe, due to genetic heterogeneity, age, or the presence of comorbidities in the population worldwide, the prediction of severe adverse outcome in patients remains a challenge. To elucidate Spike proteins underlying patient‐specific‐vascular thrombosis, the human microcirculation environment is recapitulated using a novel microfluidic platform coated with human endothelial cells and exposed to patient specific whole blood. Here, the blood coagulation effect is tested after exposure to Spike protein in nanoparticles and Spike variant D614G in viral vectors and the results are corroborated using live SARS‐CoV‐2. Of note, two potential strategies are also examined to reduce blood clot formation, by using nanoliposome‐hACE2 and anti‐Interleukin (IL) 6 antibodies. Abstract : SARS‐CoV‐2 infection drives the increasingly recognized thrombotic complications in COVID‐19 patients, potentially due to the SARS‐CoV‐2 Spike protein binding to human angiotensin‐converting enzyme 2. Vaccination therapies that are spike‐based can lead to a similar outcomes. Endothelialized channels exposed to patient specific blood in microfluidic platforms can be used to rapidly test for blood coagulation, predicting thrombotic events.